Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1462-2920.2005.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the genomes of archaea mediating the anaerobic oxidation of methane

Abstract: The anaerobic oxidation of methane is a globally significant process which is mediated by consortia of yet uncultivated methanotrophic archaea (ANME) and sulfate-reducing bacteria. In order to gain deeper insights into genome characteristics of the different ANME groups, large-insert genomic libraries were constructed using DNA extracted from a methanotrophic microbial mat growing in the anoxic part of the Black Sea, and from sediments above gas hydrates at the Hydrate Ridge off the coast of Oregon. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 76 publications
2
84
0
Order By: Relevance
“…In addition, phylogenetically distinct subgroups of the ANME-2 (a, b, and c) appear to exhibit specific habitat preferences and unique spatial configurations with sulfate-reducing bacteria related to Desulfosarcina (DSS) (16,17), suggesting that the ANME-2 subgroups represent unique ecotypes. Metagenomic sequencing of the microbial community in methane seep sediment has shed light on the physiology and specific mechanism of AOM catalyzed by some of the ANME archaea (18,19). However, details of the metabolic regulation, environmental adaptation, and intracellular communication of these diverse archaea and their bacterial partners are still largely unexplored.…”
Section: Syntrophy and The Anaerobic Oxidation Of Methane And Microbimentioning
confidence: 99%
“…In addition, phylogenetically distinct subgroups of the ANME-2 (a, b, and c) appear to exhibit specific habitat preferences and unique spatial configurations with sulfate-reducing bacteria related to Desulfosarcina (DSS) (16,17), suggesting that the ANME-2 subgroups represent unique ecotypes. Metagenomic sequencing of the microbial community in methane seep sediment has shed light on the physiology and specific mechanism of AOM catalyzed by some of the ANME archaea (18,19). However, details of the metabolic regulation, environmental adaptation, and intracellular communication of these diverse archaea and their bacterial partners are still largely unexplored.…”
Section: Syntrophy and The Anaerobic Oxidation Of Methane And Microbimentioning
confidence: 99%
“…Subunits HdrC and HdrB are also conserved in subunit TfrB of thiol:fumarate reductase (TFR) (Figure 1), an anabolic enzyme of methanogens that catalyzes the reduction of fumarate to succinate with CoM-SH plus CoB-SH as electron donors (10). HDR with highly conserved HdrB and HdrC subunits is also encoded by the genomes of uncultivated anaerobic methanotrophic archaea in which the enzyme is thought to catalyze formation of CoM-S-S-CoB from CoM-SH and CoB-SH during anaerobic methane oxidation (11).…”
mentioning
confidence: 99%
“…Solvent A was water with 0.1% formic acid, and solvent B was methanol with 0.1% formic acid. The flow rate was 0.5 ml/min, and gradient elution was employed in the following manner: (time [min], percent solvent B): (0.01, 5), (10,65), and (15,65). Ten microliters of sample was injected.…”
Section: Methodsmentioning
confidence: 99%
“…The chemically challenging activation of methane by ANME occurs via a reversal of the MCR-catalyzed step in methanogenesis (16). Metagenomic data have shown that ANME possess homologs of MCR as well as most genes normally associated with methanogenic archaea, indicating that these organisms oxidize methane using a pathway which is essentially methanogenesis in reverse (15,17). A modified form of F 430 , F 430 -2 ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation